Proxidant And Antioxidant Status In Type 2 Diabetes With Relation To Its Duration - VIVIAN SAMUEL T (International Journal of Pharma and Bio Sciences, 2011)
Diabetic patients are exposed to increased oxidative stress due to several mechanisms, including glucose auto-oxidation and non enzymatic protein glycation. The aim of the present study was to evaluate the levels of selected oxidation and antioxidant status in type 2 diabetes and to correlate the lipid peroxidation and antioxidant with duration of diabetes and glycemic control. Degree of lipid peroxidation in terms of serum malondialdehyde (MDA), along with enzymatic antioxidants (ie, superoxide dismutase (SOD) and free radical scavengers ie, reduced glutathione (GSH) and vitamin C were estimated in 60 controls and 89 type 2 diabetic patients. Analysis was done using Unpaired‘t’ test, for comparison between two groups and One way ANOVA (F-test) for multiple group comparison. FBS, serum MDA levels of diabetic patients were significantly higher (p<0.001), whereas SOD, GSH, Vit C, levels were significantly lower relative to their controls (p<0.001). There was a highly significant p<0.001 increase in the mean levels of FBS and MDA in NIDDM patients whereas SOD, GSH, Vit C shows a statistically significant decrease with the both glycemic control and the duration of diabetes. Certain indices of oxidant stress are influenced by the duration of diabetes and the efficacy of glycemic control. These observations suggest that supportive therapy aimed at oxidative stress may help to prevent clinical complications in type 2 diabetes mellitus.